Investigating Transitivity and Text Types in EFL Textbook "English for Nusantara" - Annisa Jihan Salsabil; Agus Widyantoro; Margana Margana; Ashadi Ashadi (Journal of English Language Teaching and Linguistics, 2025)
The several kinds of operations about the concepts or content supplied in the phrase are addressed by the grammatical system known as transitivity. The generation of the situation's field might explained by looking at the texts' transitivity structure. This study aims to analyze a transitivity pattern and its suitability with the communicative goals of various types of texts in the EFL English for Nusantara textbook. The focus of this research is on examining the type of process, the role of the participants, and the elements of information to understand how these linguistic features able to contribute to achieving the goal of communicative effectiveness in a narrative, descriptive, recount, procedural, and expository text. This research uses a qualitative descriptive approach, with content analysis as the primary method. Data might be collected by systematically identifying linguistic characteristics in texts that have been selected, followed by categorization and interpretation. This methodology provides the possibility of an in-depth understanding of how linguistic characteristics have an appropriate role in accordance with their communicative purposes. The results of the study provide clues that each type of text has different transitivity patterns according to its function. Narrative texts are dominated by material processes, emphasizing actions and events, while relational and mental processes may add context and depth. Descriptive text provides insight into the balance of relational processes with material. Recount texts emphasize material processes to tell past events dynamically. Procedural texts focus on material processes to provide instructions and achieve real results, while expository texts might provide a balance between material and relational processes to present and explain information.